Counseling on Iron Deficiency Anemia in Pregnant Women as an Effort to Prevent Stunting in Sukasirnarasa Village - Sitompul, Yunita R.M.B; Sintabella, Amanda; Novelyn, Silphia; Putra, Benaya; Apriliani, Lucyana Lettisia (CV. Inara, 2025)
Stunting and anemia are quite serious public health problems, especially in areas with high poverty rates and limited access to health services. Several contributing factors include lack of knowledge about nutrition, unbalanced diets, and limited access to health services. One of the factors that contributes to stunting is anemia in pregnant women. Given these conditions, efforts are needed to increase public understanding of anemia and stunting and prevent stunting from pregnancy. These efforts were realized through health education activities carried out in September 2023 in Sukasirnarasa Village, Sumedang Regency, West Java. Participants were 10 posyandu cadres and pregnant women. The service activity was in the form of education about iron deficiency anemia. The success of this activity was evaluated through measuring achievement indicators using a pretest and posttest with a true-false test type. The evaluation results showed an increase in participant understanding by 15.7% after participating in the education. This increase indicates that health education activities regarding stunting prevention through anemia prevention in pregnant women have been successfully implemented and achieved the expected goals..